Design-for-Test and Test Optimization Techniques for TSV-based 3D Stacked ICs - Noia, Brandon; Chakrabarty, Krishnendu (Springer International Publishing : Imprint: Springer, 2014)
This book describes innovative techniques to address the testing needs of 3D stacked integrated circuits (ICs) that utilize through-silicon-vias (TSVs) as vertical interconnects.  The authors identify the key challenges facing 3D IC testing and present results that have emerged from cutting-edge research in this domain.  Coverage includes topics ranging from die-level wrappers, self-test circuits, and TSV probing to test-architecture design, test scheduling, and optimization.  Readers will benefit from an in-depth look at test-technology solutions that are needed to make 3D ICs a reality and commercially viable.   • Provides a comprehensive guide to the challenges and solutions for the testing of TSV-based 3D stacked ICs; • Includes in-depth explanation of key test and design-for-test technologies, emerging standards, and test- architecture and test-schedule optimizations; • Encompasses all aspects of test as related to 3D ICs, including pre-bond and post-bond test as well as the test optimization and scheduling necessary to ensure that 3D testing remains cost-effective.  .